1971
DOI: 10.1073/pnas.68.5.1028
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Spectrum of Lysine-Vasopressin and Its Structural Implications

Abstract: The NMR spectra at 220 MHz of iysinevasopressin and its precursors were measured in dimethyl sulfoxide, and the peaks were assigned to specific protons. Information about hydrogen bonding was obtained from the temperature coefficients of the chemical shifts. With these data, and with several chemical-shift positions and coupling constants, structural information was derived for this polypeptide hormone.High-resolution nuclear magnetic resonance (NMR) studies offer the possibility of determining the conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Clearly, the 20-membered ring compounds by themselves have conformations quite different from that proposed (6,16) for the parent hormone and deamino analog. Provided that solvent effects prove unimportant, this result would suggest the formation of a different kind of ring structure for oxytocin and deamino-oxytocin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the 20-membered ring compounds by themselves have conformations quite different from that proposed (6,16) for the parent hormone and deamino analog. Provided that solvent effects prove unimportant, this result would suggest the formation of a different kind of ring structure for oxytocin and deamino-oxytocin.…”
Section: Discussionmentioning
confidence: 99%
“…The use of nuclear magnetic resonance (NMR) to study the structural features of cyclic polypeptides is well established (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Information concerning various conformational features, including peptide backbone structure, rigidity, and presence of intramolecular hydrogen-bonding is obtained by this method.…”
mentioning
confidence: 99%
“…It has been reported that the Tyr NH absorption in spectra of oxytocin and Lys-VP broadens when they are recorded in [U-2H]Me2SO (1,2,16 (Fig. 3) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation of neurohypophyseal hormones by '3C NMR spectroscopy promises, therefore, to yield valuable information in extending past conformational studies of these peptides by thin-film dialysis (39), chromatographic methods (40), circular dichroism (41), minimization energy calculation (42), and proton NMR (1)(2)(3)(4)(5)(6)(7)(43)(44)(45)(46)(47) (31,48,49) and D20 (31,48) (4, 7). In making the assignments it was assumed that the order of 'IC resonances of the hormones was the same as in the acyclic nonapeptide for all residues except cysteine.…”
mentioning
confidence: 99%
“…Conformational analysis of data from proton nuclear magnetic resonance ('H NMR) spectroscopy has contributed significantly to elucidation of the preferred solution conformations of oxytocin (1,2) and lysine vasopressin ([Lys8]VP) (3)(4)(5)(6)(7). Nevertheless, the conformational analysis involves several approximations: (1) the relationship between the dihedral angle 0 (NH-CaH) and the measured three-bond coupling constant 3JHNCH (8,9)-a spectral parameter most useful when considered in combination with potential energy maps (10,11); (2) temperature (12) and solvent (13,14) dependences of chemical shifts and proton exchange rates (15)(16)(17) of peptide hydrogens as related to their solvent-exposed or solvent-shielded state.…”
mentioning
confidence: 99%